Are Feeding Modes Concealing Morphofunctional Diversity? The Case of the New World Parrotfishes - Pombo-Ayora, Lucía; Tavera, Jose (Frontiers in Marine Science, 2021)
In functional ecology, morphology is expected to reflect function; however, occasional decoupling of these two can be found. In the case of feeding ecology, the diversity of the diet or diversity of the feeding modes within a clade is expected to be positively related to the diversity of the morphological traits involved in the feeding performance. Parrotfishes are separated into two main groups, the "reef" clade and the "seagrass" clade. Both groups have important differences in their evolutionary history. Still, more interestingly, they have important morphological and ecological differences. The genera Scarus and Sparisoma are the most specious genera of parrotfishes. They belong to each of those main groups, respectively. All Scarus species have the same feeding mode, while in Sparisoma, there are three different feeding modes. We want to test if the morphological jaw diversity of these genera corresponds with the diversity in their feeding modes. Using a disparity analysis of feeding traits within a phylogenetical framework, we did not find a relationship between functional feeding morphology and feeding modes of the American parrotfishes of the genera Scarus and Sparisoma. Interestingly we found that some muscular traits are the source of the high disparity in the genus Scarus. We explore some possible morpho-functional reasons for this phenomenon and reappraise the parrotfishes' scraper feeding mode's functional diversity. We also consider that there could be more ecological differentiation between Scarus species that we are aware of. Using an ancestral reconstruction of feeding modes of 52 species of parrotfishes, we found that the scraping feeding mode exhibited by all Scarus species is an evolutionary convergence with the scraping feeding modes performed by some Sparisoma species. Different selective pressures or ecological conditions may have shaped the differences in the feeding ecology and the feeding morphology of these two genera. Probably, key novel structures and muscular properties found in the Scarus species' jaw played an essential role in this genus's morpho-functional diversification. Finally, we propose that feeding modes may not fully capture the complexity of feeding ecology in parrotfishes.